Produk Hukum Pengkebirian Pemerintahan Desa - -, Sarip (Jurnal Hukum & Pembangunan, 2019)
This article aims to examine Law Number 6 of 2014 concerning Villages relating to the castration of villages through legal products issued by the state. Refuse of Article 18B Paragraph (2) The 1945 Constitution of the state recognizes and respects customary law community units and their constitutional rights insofar as they are still alive and in accordance with the development of society and the principle of the Unitary State of the Republic of Indonesia, which is regulated in law. The castration of the village is basically a means that cannot be fully blamed or justified. These considerations are of concern to those who understand the importance of the integrity of the country. The implementation is very contradictory where villages must submit to the commands that have been determined by legal products